PHARMACOECONOMIC ANALYSIS OF DOCETAXEL IN THE ADJUVANT THERAPY OF BREAST CANCER - R. I. Yagudina; I. Yu. Zinchuk (Фармакоэкономика)
Based on a clinical study BCIRG 001 (Martin M., Mackey J., Pienkowski T.) and as an outcome of Markov simulation it was determined that the use of 6DAC for adjuvant therapy in 10 year horizon of research allows to increase the disease-free survival by 6,09%, and overall survival by 5,88% comparing to 6FAC. Use of 6DAC instead of 6FAC allows to reduce the number of patients with local relapse, regional relapse and metastasis insignificantly as well. In the result of direct costs analysis it was determined that for 10-years horizon cost rate for the treatment of one patient with breast cancer will be 1 198 300 RUB for 6DAC and 1 371 184 RUB for 6FAC. Direct and indirect costs rate of the breast cancer treatment were 1 683 844 RUB and 1 973 043RUB for the 6DAC and 6FAC schemes respectively. It was determined that the scheme of adjuvant therapy that includes Docetaxel besides of addition efficiency, allows to reduce the cost rate to 289 199 RUB in 10 years.